Institutionen, Regulation und Geographie - Berndt, Christian (ERDKUNDE, 1999)
This paper argues that because of its still largely unresolved conceptual shortcomings, regulation theory can only with difficulties be applied empirically. These conceptual gaps concern, first, an undertheorised account of the micro- and meso-level of social action and, second, a neglect of the way in which processes of institutionalisation and regulation are spatially mediated. As regards the former, an alternative perspective is developed which draws upon recent developments within institutional economics in explaining the co-ordination and regularisation of economic processes. Here, it is the revival of classical institutional thought and as such a heterodox, sociological institutionalism rather than neoclassical transaction cost theory which serves as a source of inspiration. With a view to the neglect of space, economic geographers have largely passively followed the recent convergence between branches of economics and the social sciences and have missed the opportunity to influence the interdisciplinary debate. This paper seeks to show that geography can make an original contribution to this interdisciplinary convergence. This can be achieved by adopting a contextual and relational view of space and place, starting with globalisation as a dynamic process which questions institutionalised relations and rearticulates power configurations. It is through the contradictory unity of proximity and distance, of mobility and immobility, of inclusion and exclusion that geography mediates processes of institutionalisation and regulation. This allows us to refute conceptualisations of globalisation which overstate processes of deterritorialisation and spatial homogenisation. The paper closes with the identification of themes for ‘heterodox’ geographical research. It is argued that, by focusing on issues of cultural difference, spatial incongruence and power asymmetries and their spatial mediation in an age of globalisation and transnationalisation geographers could improve the understanding of the processes at work.